Banyumas Local Government’s Failure Regarding the Garbage Management Law and Social Change : Fracaso del gobierno local de Banyumas con respecto a la ley de gestión de basura y cambio social - RIZKIDARAJAT, WIMAN; PRIMADATA, ANKARLINA PANDU (Utopía y Praxis Latinoamericana, 2021)
ABSTRACT By the end of 2016, Banyumas local government decided to shut down Tempat Pembuangan Akhir Gunung Tugel. The purpose of this paper is to show the failure of Banyumas local government to deal with the social change they made and to show legal and sociological excess caused by that failure. From a methodological standpoint, this paper operates both normative and socio-legal approaches. The results are, first, Banyumas local government unable to deal with the social change they made. Second, Banyumas local government needs a new Peraturan Daerah to substitute the prior Peraturan Daerah to improve garbage management. RESUMEN A finales de 2016, el gobierno local de Banyumas decidió cerrar Tempat Pembuangan Akhir Gunung Tugel. El propósito de este artículo es mostrar el fracaso del gobierno local de Banyumas para hacer frente al cambio social que hicieron y mostrar el exceso legal y sociológico causado por ese fracaso. Desde el punto de vista metodológico, este trabajo opera con un enfoque tanto normativo como socio-legal. El resultado es, primero, que el gobierno local de Banyumas no puede hacer frente al cambio social que hicieron. En segundo lugar, el gobierno local necesita un nuevo Peraturan Daerah para sustituir al Peraturan Daerah anterior para mejorar la gestión de basura.